2013
DOI: 10.1038/modpathol.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical stains for CD3 and CD8 do not improve detection of gluten-sensitive enteropathy in duodenal biopsies

Abstract: Patients with gluten-sensitive enteropathy usually have increased numbers of duodenal intraepithelial lymphocytes even if the villous architecture is normal. Some authors advocate the use of CD8 and CD3 immunohistochemical stains to improve detection of intraepithelial lymphocytosis, yet the added value of immunohistochemistry when biopsies appear normal remains unproven. The purpose of this study was to evaluate the utility of CD3 and CD8 immunostains in detecting intraepithelial lymphocytosis among duodenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
1
21
0
3
Order By: Relevance
“…Intraepithelial lymphocytes are active components of the mucosal immune system, the number of which increases under the influence of various antigens from the intestinal lumen (microorganisms or toxic agents). Large numbers of CD4+ lymphocytes were observed in the duodenum and at the ileocaecal junction because of local stimulation by various antigens and in relation to age and associated antigenic aggressions (Hudacko et al, 2013). Cholera toxin primarily acts through augmenting CD4+ T cell priming, leading to a strong induction of antigen-specific T cells of both the T helper Th1 and Th2 subtypes (Hörnquist et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Intraepithelial lymphocytes are active components of the mucosal immune system, the number of which increases under the influence of various antigens from the intestinal lumen (microorganisms or toxic agents). Large numbers of CD4+ lymphocytes were observed in the duodenum and at the ileocaecal junction because of local stimulation by various antigens and in relation to age and associated antigenic aggressions (Hudacko et al, 2013). Cholera toxin primarily acts through augmenting CD4+ T cell priming, leading to a strong induction of antigen-specific T cells of both the T helper Th1 and Th2 subtypes (Hörnquist et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…17 CD3+ IEL) was found in another recent study [6]. On the other hand, the routine use of immunohistochemistry is not recommended by others, because it can decrease sensitivity of observing the loss of "decrescendo pattern" [7] and in fact does not improve detection of glutensensitive enteropathy when hematoxylin and eosin-stained sections are normal [11].…”
Section: Proximal Small Bowel Iel Countmentioning
confidence: 99%
“…Although still debated, recently, Mubarak et al[49] have shown that staining for CD3 has an additional value in the histological detection of celiac disease lesions[49,50]. Immunohistochemical stains for CD3 and CD8 do not improve detection of gluten-sensitive enteropathy in duodenal biopsies.…”
Section: Histological Features Of the Celiac Diseasementioning
confidence: 99%